Implementasi Metode Diskusi berbasis Karakter untuk Meningkatkan Hasil Belajar Sastra Anak Kelas IV di MI Al Amanah Cibinong Kabupaten Bogor - Ahmad Syarif; Hasbian Gustiawati Hasan; Eda Laelasari; Agus Suryana (Jurnal Dirosah Islamiyah, 2024)
The purpose of this study was to determine the effectiveness of the application of the character-based children's literature discussion method in improving the learning outcomes of Fourth Grade Indonesian Language students at MI Al Amanah, Cibinong, Bogor Regency. The research method used is a class action research model of Kemmis and Mc Taggart's action model. The research procedure was carried out in two cycles and four stages, namely planning, implementing, observing and reflecting. The results of the study concluded that (1) The application of the character-based children's literature discussion method at MI Al Amanah, Cibinong, Bogor Regency can increase student learning activities in Indonesian language subjects. The increase in the listening aspect was 6.82%, the communication aspect was 15.91%, and the participation aspect was 6.82%. (2) The learning outcomes of Fourth Grade Students at MI Al Amanah, Cibinong, Bogor Regency have increased by 65%. (3) There is an enchancement of the application of the character-based children's literature discussion method on improving the learning outcomes of Fourth Grade Indonesian students at MI Al Amanah, Cibinong, Bogor Regency. Cycle I reached 45.45% of students completed, and in cycle II reached 100% of students completed. Thus, there is an increase of 54.55%.